Living Lab for Low-emission Food Systems Development: Report on the self-organization of the Living Lab for People (LL4P) at the Kaimosi Agricultural Training Centre, Nandi County, Kenya - Mosbei, Thomas; Kibet, Walter; Habermann, Birgit; Kachilei, Levy (2025)
This report details the self-organization and initial activities of the Living Lab for People (LL4P) at the Kaimosi Agricultural Training Centre in Nandi County, Kenya, a crucial initiative for developing low-emission food systems. Established in collaboration with the International Livestock Research Institute(ILRI), the LL4P aims to foster locally led innovation through inclusive, multi-stakeholder engagement .The report outlines the self-organization activities such as the formation of an advisory board, the process of setting an innovation agenda, and the development of an assessment framework that led to the selection of 10 innovation cases. Other key activities during this period included mental modeling workshops using fuzzy cognitive mapping and studies on gender-transformative approaches. The LL4P also actively participated in the Kaimosi ATC Agri-Expo and World Food Day 2024, showcasing innovative solutions like Azolla farming, vermicomposting, and Black Soldier Fly farming. These initiatives demonstrate the LL4P's commitment to enhancing food security, improving livelihoods, and mitigating climate change through sustainable, locally adapted practices in Nandi County.